Why is your team more creative than mine?: the influence of shared mental models on intragroup conflict, team creativity and effectiveness - Santos, C. M. (2016)
In competitive and dynamic contexts team members need to be creative to ensure that teams achieve high levels of performance and feel satisfied with their work. At the same time, team members need to have a shared understanding regarding relevant aspects related to task accomplishment and team interaction. In this study we investigate the mediating mechanisms of intragroup conflict and creativity in the relationship between shared mental models and team effectiveness (team performance and satisfaction). We tested our model in a sample of 161 teams (735 individuals) performing in a management simulation. We collected data at three time points. Our results suggest that high shared mental models are related to low levels of intragroup conflict, foster creativity, and in turn improve team performance and satisfaction. These findings contribute to a scarce thematic – the relationship between shared mental models and creativity – emphasizing the importance of a shared understanding for creativity and team effectiveness.